Analyzing policy processes as complex systems: The case of Mesoamerican Sustainable Development Initiative.Analyzing policy processes as complex systems: Mesoamerican Sustainable Development Initiative. - Almaguer-Kalixto, Patricia; Amozurrutia, José A.; Marcuello Servós, Chaime (Journal of Sociocybernetics, 2014)
This paper presents a research methodology for analyzing policy processes that are defined at the global level but implemented locally. The interrelations between these two levels pose great conceptual challenges in explaining the changes, transformations and continuations occurring in this complex process based on empirical information. Understanding the policy process as a complex system, this paper proposes analyzing macro, meso and micro levels as subsystems of the total process, identifying the interrelations between policy action, actors and discourses. The paper takes the example of the Mesoamerican Sustainable Development Initiative (MSDI) of the Puebla Panama Plan (PPP), a regional integration plan for a new ‘Mesoamerica’ that originally included the seven Central American countries and the southern states of Mexico.